Open surgical retrieval of ovarian migrated intrauterine contraceptive device: a case report - Bobo, Temidayo I.; Popoola, Adetomilola K.; Duke-Aluko, Gloria A.; Ano-Edward, Gbemi H.; Bakare, Tola Y. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Intraovarian migration of intrauterine contraceptive device (IUD) is a rare complication, only few cases have been reported. Arguably no reported case in Nigeria to best of knowledge. The patient was Mrs. S.I, a 29-year-old primiparous presented with a 6-hour history of abdominal pain, the pain was said to be sudden in onset pain associated with vomiting. She used an IUD for contraception for about 2 years prior to her presentation. The physical examination showed a patient with good hemodynamic and ventilatory status. Abdominal and vaginal examination revealed marked tenderness at suprapubic and left iliac region, with positive cervical excitation and left adnexal tenderness respectively. Provisional diagnosis of acute pelvic inflammatory disease was made, empirical broad spectrum antibiotic therapy commenced, pelvic scanning done revealed a hyperechoic structure, likely intrauterine device, perforating the uterine fundus and extending into the left ovary. Subsequently, she had laparotomy and the removal of the device. She did well post-surgery and was discharged home to follow in the clinic on the third day after surgery. Intraovarian migration of IUD is one of the rare complications of the device. High index of suspicion with radiological imaging support is necessary in making the diagnosis in a woman of reproductive age group with IUD in- situ regardless of the visible IUD string or not.